MALDI-TOF MS identification of microbiota associated with pest insect Diabrotica speciosa - Perlatti, Bruno; Luiz, Anderson L.; Prieto, Evandro L.; Fernandes, João B.; da Silva, Maria Fátima das Graças Fernandes; Ferreira, Douglas; Costa, Eduardo N. [UNESP]; Boiça Júnior, Arlindo L. [UNESP]; Forim, Moacir R. (Wiley, 2017)
Resistance development in pest insects has guided the advance of cleaner and more effective strategies for pest control. An interesting and promising strategy is the manipulation of insects via their gut microbiota. To evaluate the feasibility of this strategy, Diabrotica speciosa, a highly polyphagous pest insect from South America that causes substantial damage to several important crops, was reared under controlled conditions. Aerobic culturable bacteria were isolated from the gut of D. speciosa and identified using proteomic fingerprints obtained by matrix-assisted laser desorption ionization coupled to time-of-flight mass spectrometry (MALDI-TOF MS), as well as by genomic methods via partial sequencing of the 16S rRNA gene. Seventy-three strains belonging to 17 genera and up to 29 different species were isolated. γ-Proteobacteria of the orders Pseudomonadales and Enterobacteriales were the predominant. A core gut microbiome for the genus Diabrotica could be inferred when microbiotas from different species from the genus were compared. Molecular and spectrometric techniques indicated complete agreement of genera classification, although cluster analysis revealed distinct taxonomic grouping patterns. MALDI-TOF MS provided reliable identification of culturable gut bacteria, demonstrating similar efficacy, with cheaper and faster results relative to partial 16S rRNA gene sequencing, and also showed an interesting and unexpected phyloproteomic correlation.
Keywords: Diabrotica speciosa; gut bacteria; MALDI-TOF MS; microbial ecology; phylogenetic; phyloproteomic